A parallel Numerical Algorithm For Solving Some Fractional Integral Equations - Mohammed Al-Abrahemee, Khalid Mindeel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this study, He's parallel numerical algorithm by neural network is applied to type of integration of fractional equations is Abel’s integral equations of the 1st and 2nd kinds. Using a Levenberge – Marquaradt training algorithm as a tool to train the network. To show the efficiency of the method, some type of Abel’s integral equations is solved as numerical examples. Numerical results show that the new method is very efficient problems with high accuracy.